Softening Competition by Enhancing Entry: An Example from the Banking Industry - Jan Bouckaert; Hans Degryse (Center for Economic Studies and ifo Institute (CESifo), 2002)
We show that competing firms relax overall competition by lowering future barriers to entry. We illustrate our findings in a two-period model with adverse selection where banks strategically commit to disclose borrower information. By doing this, they invite rivals to enter their market. Disclosure of borrower information increases an entrant's second-period profits. This dampens competition for serving the first-period market
Keywords: 330; barriers to entry; asymmetric information; switching costs; banking competition.